2020
DOI: 10.1002/slct.202004034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Evaluation of Benzimidazole Derivatives Having Norbornene/Dibenzobarrelene Skeletons and Different Functional Groups

Abstract: Two different anhydrides having norbornene and dibenzobarrelene skeletons were synthesized from Diels‐Alder cycloaddition reactions using dienes such as anthracene and cyclopentadiene, and dienophiles like maleic acid and maleic anhydride. New benzimidazole derivatives bearing carboxamide, guanidine, and cyclic imide functional groups were obtained from these anhydrides. The compounds were investigated for their effects on MDA‐MB‐231 (Human breast cancer), A549 (Lung cancer), Ovcar3 (Human Ovarian cancer), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(45 reference statements)
0
2
0
1
Order By: Relevance
“…[10] In our previous studies, we focused on the synthesis of new benzimidazole derivatives, [11] some physical properties determination, [12] and their biological activities investigation, especially as HSP90 inhibitors. [2,13] In the continuation of our studies on biologically active benzimidazole derivatives, the microwave-irradiation synthesis methods and theoretical re-search results of new 1,3,4-thiadiazole and 1,2,4-triazole derivatives containing unsubstituted benzimidazole were reported for the first time in this study. All reactions which require heating were performed by both conventional and microwave-assisted methods.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…[10] In our previous studies, we focused on the synthesis of new benzimidazole derivatives, [11] some physical properties determination, [12] and their biological activities investigation, especially as HSP90 inhibitors. [2,13] In the continuation of our studies on biologically active benzimidazole derivatives, the microwave-irradiation synthesis methods and theoretical re-search results of new 1,3,4-thiadiazole and 1,2,4-triazole derivatives containing unsubstituted benzimidazole were reported for the first time in this study. All reactions which require heating were performed by both conventional and microwave-assisted methods.…”
Section: Introductionmentioning
confidence: 82%
“…It is considered an important bioactive heterocyclic building block for the discovery of new pharmacological active agents in medicinal chemistry, such as antimicrobial, antiviral, antidiabetic, and anticancer activity. [2] Besides, benzimidazoles are remarkably effective compounds, extensive biochemical and pharmacological studies have confirmed that these molecules are effective against various strains of micro-organisms. [3] 1,3,4-thiadiazole and 1,2,4-triazole are important five-membered nitrogen-containing heterocyclic compounds with a wide range of applications in organic synthesis and pharmaceutical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Два разных ангидрида, содержащие фрагменты норборнена и дибензобаррелена, были синтезированы в результате реакций циклоприсоединения Д-А с использованием диенов, таких как антрацен и циклопентадиен, и диенофилов, таких как малеиновая кислота и малеиновый ангидрид [3]. Из этих ангидридов были получены новые производные бензимидазола, несущие карбоксамидные, гуанидиновые и циклические имидные функциональные группы.…”
unclassified